Male sex ratio of red tilapia Oreochromis sp. after soaking in different concentrations of coconut milk at larvae stadia - Fajar Maulana; Agus Oman Sudrajat; Andre Permana; Lina Mulyani; Harton Arfah (Jurnal Akuakultur Indonesia)
Tilapia has sexual dimorphism, based on the size and growth. Male tilapia has a faster growth rate than female tilapia. Masculinization can be carried out to produce monosexual tilapia seeds to accelerate fish growth. As the use of the 17α-methyltestosterone synthetic hormone for masculinization activities has been limited, natural ingredients are required as a substitute, namely coconut milk. This study aimed to determine the effect of different coconut milk concentrations as a phytosteroid material for the masculinization of red tilapia by immersing the larvae to the material. Tilapia fish larvae were immersed in coconut milk for 12 hours and then reared for 60 days at 100 larvae for each rearing container. There were four different treatments, namely control treatment without coconut milk immersion, S3 (3 ml/L coconut milk), S5 (5 ml/L coconut milk), and S7 (7 ml/L coconut milk). The results showed that the 7 ml/L coconut milk treatment increased the male sex ratio and specific growth rate and reduced the feed conversion ratio without a negative impact on the survival rate of red tilapia fry. In this study, the 7 ml/L coconut milk treatment was the best treatment, which produced a male sex ratio of 67.78 ± 4.16%.